Review of microbial touchscreen contamination for the determination of reasonable ultraviolet disinfection doses - Hessling, Martin; Haag, Robin; Sicks, Ben (German Medical Science GMS Publishing House, 2021)
Background: Touchscreens are usually microbially contaminated and can therefore act as fomites inside and outside healthcare environments. Due to the increasing use of such touchscreens and the growing awareness of infection risks, approaches that allow safe and automatic disinfection are desired. Ultraviolet (UV) irradiation, with its known antimicrobial efficacy, could achieve this goal, but should be executed with limited touchscreen degradation, disinfection duration, and energy consumption. It should also pose as little harm as possible to humans even in case of failure. Materials and methods: A literature search was performed first to identify the microorganisms most commonly found on touchscreens. Then, the 90% reduction doses (D90 doses) for the different relevant microorganisms and UV spectral ranges were determined from the literature, and irradiation doses are suggested that should reduce most of these important microorganisms by 5 log-levels. Results: The most frequent microorganisms are staphylococci, bacilli, micrococci, enterococci, pseudomonads and with small differences between hospital and community environments, if antibiotic resistance properties are ignored. The determined irradiation doses for a 5 log-reduction of the most frequent microorganisms are about 4, 80 J/cm, 500 J/cm and 50 mJ/cm for the UV spectral ranges UVC, UVB, UVA and far-UVC, respectively. These doses are also sufficient to inactivate all nosocomial ESKAPE pathogens on touchscreens by at least 99.999%.Conclusion: Disinfection is achievable in all UV spectral ranges, with UVC being the most effective, enabling automatic disinfection within a minute or less. The much higher doses required in the UVB and UVA spectral range result in much longer disinfection durations, with the advantage of a reduced risk to humans. For all kinds of UV irradiation, the doses should be limited to reasonable values to avoid irradiating an already more or less sterile surface and to prevent degradation of touchscreen devices.